Jurnal Akuntansi & Investasi: Analisis Komparatif Kinerja Keuangan Perbankan Syariah Menggunakan Metode Camels pada Sebelum, Selama dan Sesudah Krisis Global Tahun 2008 - Suci Kurniawati (Akuntansi FE UMY, 2012)
In 2008 the global financial crisis that hit the United States has spread to the whole world. Conditions of the global economic crisis affecting the financial performance of banks and each bank has the financial performance of the condition varies in receiving the impact of global crisis include Shariah banking